1996
DOI: 10.1016/0014-5793(96)00920-9
|View full text |Cite
|
Sign up to set email alerts
|

Removal of proteasomes from the nucleus and their accumulation in apoptotic blebs during programmed cell death

Abstract: Apoptosis can be initiated in immortalized cAMPstimulated rat ovarian granulosa cells by induction of wild-type p53 activity, lmmunocytochemical studies using confocal microscopy reveal that in apoptotie, unlike in normal growing cells, the proteasomes are removed from the nucleus and accumulate within the apoptotic blebs at the periphery of the cell. In parallel, a striking reorganization of the actin cytoskeleton is observed which forms a spherical network separating the apoptotic blebs from the cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 26 publications
8
18
0
Order By: Relevance
“…Figure 8 A shows that within 6 hr after the apoptotic stimulus, a progressive increase of a heterogeneous population of high molecular weight proteins is detectable in the cytoplasmic extracts. Notice that at 12 hr after the onset of apoptosis, whereas the extent of dying neurons continues to increase and approximates 50% of total neurons, the amount of ubiquitinated polypeptides is lower than that detectable at 6 hr, probably because of the sequestration of proteasome and ubiquitinated proteins in the apoptotic blebs as previously described (Pitzer et al, 1996). A different trend is observed for nuclear proteins, because during the same period a progressive reduction in the ubiquitin immunostaining occurs.…”
Section: Accumulation Of Ubiquitinated-proteins In Cerebellar Granulesupporting
confidence: 52%
“…Figure 8 A shows that within 6 hr after the apoptotic stimulus, a progressive increase of a heterogeneous population of high molecular weight proteins is detectable in the cytoplasmic extracts. Notice that at 12 hr after the onset of apoptosis, whereas the extent of dying neurons continues to increase and approximates 50% of total neurons, the amount of ubiquitinated polypeptides is lower than that detectable at 6 hr, probably because of the sequestration of proteasome and ubiquitinated proteins in the apoptotic blebs as previously described (Pitzer et al, 1996). A different trend is observed for nuclear proteins, because during the same period a progressive reduction in the ubiquitin immunostaining occurs.…”
Section: Accumulation Of Ubiquitinated-proteins In Cerebellar Granulesupporting
confidence: 52%
“…F-actin increases after exposure to H 2 O 2 (27) and is present at the base of the blebs during apoptosis. 43,44 In endothelial cells tyrosine phosphorylation of cortactin, an F-actin-binding protein, is required for H 2 O 2 -induced blebbing and is also found in the blebs themselves. 24 Also, transmission electron microscopy of thyroid cells showed the assembly of 6-nm microfilaments at the base of the blebs, 45 and confocal sectioning of suprastimulated pancreatic cells showed that actin and myosin II localized at the basolateral membrane leaving breaks centered at the neck of the blebs.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the possible interaction of p53 with actin filaments (39,40), we tested the effects of cytochalasin B on the ET-1-induced responses. Cytochalasin B, at the concentration (1 M) high enough to block the ET-1 (5 nM)-induced actin reorganization, failed to block the p53 translocation and apoptotic cell death (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ET Bmediated actin reorganization seemed rather independent from the apoptotic cell signaling. Pitzer et al (40) described p53-induced apoptosis of rat ovarian granulosa cells associated with actin reorganization and indicated the role of nuclear proteosomes translocated into the cytoplasm in the latter response. It remains to be determined whether the ET B -mediated actin reorganization is due to the activation of signaling pathway that parallels the apoptotic signaling or is secondary to p53 mobilization.…”
Section: Discussionmentioning
confidence: 99%